Analisis Perlindungan Hukum Koperasi dalam Kasus Wanprestasi Atas Hutang Debitur Berdasarkan Putusan Nomor 4/Pdt.G/PN BJN - Tata Defi (Jurnal Hukum Lex Generalis, 2025)
Cooperatives are a form of group of people and also legal enities that have a joint work system in a family principle for the common interest, in a cooperative there is an agreement both from the community and cooperative members, therefore this agreement is to bind the parties who have a common interest. There is an impact arising from an agreement both in achievement and deault where every agreement made in this cooperative always raises the law for that there needs to be legal efforts to proctect the rights of the cooperative. This research aims to find out about legal protection efforts for cooperatives that are defaulted by debtors.